Joseph Chamberlain entrepreneur in politics - Marsh, Peter T. (Yale Univ. Press, 1994)
The vast range of Chamberlain's life has defeated many previous biographers. After twelve years of exhaustive study in archives around the globe, Marsh has produced the first full, archivally-based, single-volume account. Skillfully dissecting the political career, he reveals Chamberlain's radically individual approach to most of Britain's problems between the Second Reform Act and the First World War. Marsh highlights too the distortions and discontinuities: the breach with Gladstone over Irish Home Rule, which drove Chamberlain from the left of the Liberal party into enduring alliance with the Conservative right; the scourge of the House of Lords who became its champion; the free trader who died a protectionist. And he explains the internationalism, the involvement in South Africa, Canada and the United States, and the sustained campaign to develop the British Empire's 'undeveloped estates'
Keywords: Chamberlain, Joseph; Chamberlain, Joseph <1836-1914>; Chamberlain, Joseph -- 1836-1914; Geschichte 1870-1914; Hommes d'État - Grande-Bretagne - Biographies; Industriels - Grande-Bretagne - Biographies; Politik; Industrialists -- Great Britain -- Biography; Statesmen -- Great Britain -- Biography; Grande-Bretagne - Politique et gouvernement - 1837-1901; Grande-Bretagne - Politique et gouvernement - 1901-1910; Großbritannien; Great Britain -- Politics and government -- 1837-1901; Great Britain -- Politics and government -- 1901-1910; Biografie